A greyhound of a girl - Doyle, Roddy, 1958- (London : Marion Lloyd Books, 2011)
"Mary O'Hara is a sharp and cheeky twelve-year-old Dublin schoolgirl who is bravely facing the fact that her beloved Gran is dying. But Gran can't let go of life, and when a mysterious young woman turns up in Mary's street with a message for her Gran, Mary gets pulled into an unlikely adventure"--Provided by publisher.
3.0
5-8.
5-8
Keywords: Apparitions -- Juvenile fiction; Death -- Juvenile fiction; Grandmothers -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Death -- Fiction; Ghosts -- Fiction; Grandmothers -- Fiction; Mothers and daughters -- Fiction; Voyages and travels -- Fiction; Death -- Fiction; Ghost stories; Grandmothers -- Fiction; Mother-daughter relationship -- Fiction; Voyages and travels -- Fiction; Dublin (Ireland) -- Juvenile fiction; Ireland -- Juvenile fiction; Dublin (Ireland) -- Fiction; Ireland -- Fiction; Dublin (Ireland) -- Fiction; Ireland -- Fiction; Ghost stories